ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA DENGAN MODEL POLYA - hasibuan, Ainul marhamah; Yusrizal, Yusrizal; Nadawiya, Nadia; Safira, Elasa (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to analyze Student Errors in Solving Mathematics Problems with the Polya Model in SMA PAB 5 students. The approach used is a qualitative approach with a descriptive research type. Data collection using tests and interviews. This study involved 24 students in class X-1. Subjects for the interview were taken from 3 of 24 students in class X-1, with the criteria of students who made mistakes in solving mathematics problems with the material of the three-variable linear equation system (SPLTV). Each research subject was interviewed regarding the results of the questions that had been solved. Data validity testing was carried out using time triangulation. The results of the study showed that there were mistakes made by class X students of SMA PAB 5. The mistakes made in solving mathematical story problems on the SPLTV material were mistakes in understanding the problem, mistakes in making problem-solving plans, mistakes in implementing plans, and mistakes in rechecking answers. The type of error that is most often made is an error in implementing the plan. The factor that causes students to make mistakes is that students have difficulty understanding the meaning of the sentence in the story problem.